Requirements engineering problems in 63 software companies in Malaysia - Solemon, Badariah; Sahibuddin, Shamsul; Abd Ghani, Abdul Azim (IEEE, 2008)
It is widely acknowledged that problems associated with Requirements Engineering affect the quality of software and the effectiveness of the software development process. Malaysia is fast becoming an IT outsourcing heaven yet there is a lack of published studies on these problems in the region. This paper presents exploratory survey results of project and Requirements Engineering problems as identified by 63 Malaysian software development companies.